2013
DOI: 10.1111/apha.12087
|View full text |Cite
|
Sign up to set email alerts
|

Postural influences on the mechanical and neural components of the cardiovagal baroreflex

Abstract: Cardiovagal baroreflex sensitivity in response to rising pressures is reduced in young individuals during postural stress. Our data suggest that the mechanical component is unaffected by standing, and the reduction in baroreflex sensitivity is driven by the neural component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…We have previously shown that posture significantly affects cardiac BRS (Taylor et al. ). Furthermore, resting MSNA is lower in the supine position (Ray et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously shown that posture significantly affects cardiac BRS (Taylor et al. ). Furthermore, resting MSNA is lower in the supine position (Ray et al.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the methods used may explain the discrepancy with the current findings; in the study by Dutoit et al (2010) participants lay in the supine position, whereas in the current study participants were in an upright seated position. We have previously shown that posture significantly affects cardiac BRS (Taylor et al 2013). Furthermore, resting MSNA is lower in the supine position (Ray et al 1993), which may reduce the number of MSNA bursts with which to produce a sympathetic baroreflex slope.…”
Section: Relationship Between Cardiac and Sympathetic Baroreflex Sensmentioning
confidence: 99%
“…However, we recently used the modified Oxford method to examine the mechanical and neural components of the cardiac baroreflex in supine and standing postures (Taylor et al . ). Our results indicate that the assumption of an upright posture is associated with significant reductions in cardiac BRS in response to rising pressures due to an attenuation of the neural component.…”
Section: Postural Influences On Baroreflex Functionmentioning
confidence: 97%
“…Integrated, mechanical and neural baroreflex sensitivity for rising pressures whilst supine (●) and standing (○) for one subject (Taylor et al . ).…”
Section: Postural Influences On Baroreflex Functionmentioning
confidence: 97%
See 1 more Smart Citation